Estudo isotópico e geomorfológico de sete reservatórios da bacia do Banabuiú - Rebouças, Jonathan Alves (2013)
Smaller reservoirs are still the main source of water of the small farmer. The sensitivity of these small water high rates of evaporation is something already well known. However, studies dealing individually these resources are still scarce. This is due to the convenience it brings to monitoring stations automatic blade evaporated by the meteorological variables. This convenience has serious consequences regarding the management of these small features, since it does not represent the geomorphological and climatic conditions in which these reservoirs are inserted. This paper conducts an individualized study of seven reservoirs that lie in the basin of Banabuiú-EC. The study is based on assessment of the geomorphological in which the reservoirs are inserted and estimating the blade evaporated for each of seven reservoirs using isotopic method. This method was suitable for the study since it intends to individualize the water body through an isotopic signature of its water. The results indicated that non-negligible differences in the amounts of evaporated blade for each reservoir, which may reach 50%. Besides the difference between the blade evaporated study shows that simplification methods used to estimate the volume stored in small tanks can overestimate them, since they have been found reservoirs with a capacity 10 times smaller but with morphometric characteristics of large reservoirs.